Needed: Financing Policies That Are Both Affordable and Sustainable - Hauptman, Arthur (International Higher Education, 2022)
Neither of the two predominant models of financing public higher education around the world manages to achieve both affordability and sustainability. Keeping tuition low provides affordability but fails to achieve financial sustainability and limits accessibility. High tuition/high aid models are more sustainable, but less affordable, resulting in more reliance on student loans. There is a consensus model that can make higher education affordable and sustainable without devoting a high percentage of GDP to higher education.